Socio-Economic Profile of Sheep Rearing Community in Bandipora District of Jammu and Kashmir - Shah, Anees Ahmad; Khan, Hilal Musadiq; Dar, Parwaiz Ahmad; Mir, Masood Saleem (Indian Journal of Hill Farming, 2018)
A survey was conducted to study the socio-economic condition of sheep rearing community in Bandipora district of Kashmir. The district was divided into low-lying(Sonawari), medium altitude (Bandipora) and High altitude (Gurez) regions. Multi-stagerandom sampling was done in which 20% villages were selected from each region in thefirst stage through proportionate random sampling and 20 respondents from each selectedvillage in second stage through simple random sampling. A total of 480 respondents(Sonawari=200, Bandipora=160, Gurez=120) from 24 villages were considered for thesurvey. It was observed that majority of the sheep rearers (59.79%) were illiterate withproportion of such respondents being significantly higher (p